The cis‐state of an azobenzene photoswitch is stabilized through specific interactions with a protein surface1. Issue 3 (9th February 2015) - Korbus, Michael; Backé, Sarah; Meyer‐Almes, Franz‐Josef; Fleminger, Gideon; Jungbauer, Alois
<x xml:space="preserve">Abstract</x> The photocontrol of protein function like enzyme activity has been the subject of many investigations to enable reversible and spatiotemporally defined cascading biochemical reactions without the need for separation in miniaturized and parallelized assay setups for academic and industrial applications. A photoswitchable amidohydrolase variant from Bordetella/Alcaligenes with the longest reported half‐life (approximately 30 h) for the cis‐state of the attached azobenzene group was chosen as a model system to dissect the underlying mechanism and molecular interactions that caused the enormous deceleration of the thermal cis‐to‐trans relaxation of the azobenzene photoswitch. A systematic site‐directed mutagenesis study on the basis of molecular dynamics simulation data was employed to investigate enzyme and thermal cis‐to‐trans relaxation kinetics in dependence on selected amino acid substitution, which revealed a prominent histidine and a hydrophobic cluster as molecular determinants for the stabilization of the cis‐isomer of the attached azobenzene moiety on the protein surface. The nature of the involved interactions consists of polar, hydrophobic, and possibly aromatic Π–Π contributions. The elucidated principles behind the stabilization of the cis‐state of azobenzene derivatives on a protein surface can be exploited to design improved biologically inspired photoswitches. Moreover, the findings open the door to highly long‐lived cis‐states of azobenzene groups yielding improved bistable photoswitches that can be controlled by single light‐pulses rather than continuous irradiation with UV light that causes potential photodamage to the employed biomolecules. Copyright © 2015 John Wiley & Sons, Ltd.